Phylogenetic and Physiological Diversity of Cultivable Actinomycetes Isolated From Alpine Habitats on the Qinghai-Tibetan Plateau - Ma, Aiai; Zhang, Xinfang; Jiang, Kan; Zhao, Changming; Liu, Junlin; Wu, Mengdan; Wang, Ying; Wang, Mingming; Li, Jinhui; Xu, Shijian (Frontiers in Microbiology, 2020)
Actinomycetes in extreme alpine habitat have attracted much attention due to their unique physiological activities and functions. However, little is known about their ecological distribution and diversity. Here, we explored the phylogenetic relationship and physiological heterogeneity of cultivable actinomycetes from near-root soils of different plant communities in the Laohu Ditch (2200 – 4200 m) and Gaize County area (5018 – 5130 m) on the Qinghai-Tibetan Plateau. A total of 128 actinomycete isolates were obtained, 16S rDNA-sequenced and examined for antimicrobial activities and organic acid, H2S, diffusible pigments, various extracellular enzymes production. Seventy three isolates of the total seventy eight isolates from the Laohu Ditch, frequently isolated from 2200 to 4200 m, were closely related to Streptomyces spp. according to the 16S rDNA sequencing, while four isolates within the genus Nocardia spp. were found at 2200, 2800, and 3800 m. In addition, one potential novel isolate with 92% sequence similarity to its nearest match Micromonospora saelicesensis from the GenBank database, was obtained at 2200 m. From the Gaize County area, fifty Streptomyces isolates varied in diversity at different sites from 5018 to 5130 m. The investigation of phenotypic properties of 128 isolates showed that 94.5, 78.9, 68, 64.8, 53, 51.6, 50, 36.7, 31.2, and 22.7% of the total isolates produced catalase, lipase 2, urease, protease, H2S, lipase 3, amylase, lipase 1, diffusible pigment and organic acid, respectively. The antimicrobial assays of the total isolates revealed that 5, 28, 19, and 2 isolates from Streptomyces spp. exhibited antimicrobial activity against Escherichia coli, Staphylococcus aureus, Candida albicans, and Pseudomonas aeruginosa, respectively. This study intends to bring helpful insights in the exploitation and utilization of alpine actinomycetes for novel bioactive compounds discovery.